2018
DOI: 10.3340/jkns.2017.0262
|View full text |Cite
|
Sign up to set email alerts
|

Surfer’s Myelopathy : Case Series and Literature Review

Abstract: Three male patients diagnosed with surfer’s myelopathy (19–30 years) were admitted to our hospital. All three patients were novice surfers showing a typical clinical course of rapid progression of paraplegia following the onset of back pain. Typical history and magnetic resonance imaging features indicated the diagnosis of surfer’s myelopathy. Two patients received high-dose steroid therapy and the other was treated with induced hypertension. One patient treated with induced hypertension showed almost full rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Surfer's myelopathy, a rare nontraumatic spinal cord injury, should also be a consideration when clinical history supports that injury is preceded by surfing, especially in novice surfers. Ischemia may contribute to its pathophysiology, and neuro‐imaging findings can be similar to SCI, but case reports show good recovery 2 . Interestingly, a study showed that specific physical maneuvers such as lifting or Valsalva preceded symptom onset in SCI in 25% of cases 3 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surfer's myelopathy, a rare nontraumatic spinal cord injury, should also be a consideration when clinical history supports that injury is preceded by surfing, especially in novice surfers. Ischemia may contribute to its pathophysiology, and neuro‐imaging findings can be similar to SCI, but case reports show good recovery 2 . Interestingly, a study showed that specific physical maneuvers such as lifting or Valsalva preceded symptom onset in SCI in 25% of cases 3 …”
Section: Discussionmentioning
confidence: 99%
“…Recognizing the challenge in SCI diagnosis, Zalewski et al 2 proposed potential diagnostic criteria for SCI based on retrospective analysis. Essentially, SCI should be considered in patients with acute nontraumatic myelopathy with onset to nadir of severe deficits occurring within 12 hours or less.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment for spinal cord infarction varies and depends on etiology. Strategies successfully used for surfer's myelopathy include hydration, induced hypertension, spinal angiography with intra‐arterial intervention, intravenous tissue plasminogen activator, and high‐dose steroid therapy . These therapies are likely to be beneficial in PSA infarction too.…”
Section: Extensive Laboratory Workup Performed To Identify Cause Of Smentioning
confidence: 99%
“…Pathologies affecting the anterior spinal artery or ASA commonly include arteriovenous malformation, vasculitis, iatrogenic causes[4], [5]. Rarer causes include hyperextension positioning[6], fibrocartilaginous embolism, thoracic disk herniation, and cervical spondylosis[7]. Anterior spinal artery syndrome (ASAS) secondary to disk herniation yields only a few cases reported so far.…”
Section: Introductionmentioning
confidence: 99%